PENGARUH MOTIVASI KERJA, BUDAYA KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI BANK TABUNGAN NEGARA (BTN) KANTOR CABANG YOGYAKARTA - Sutrisno , Erwan; Edi Setiawan (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The purpose of this study is to ascertain how workplace culture affects employee output, how work environment affects productivity, and how work motivation affects employee performance. At the Bank Tabungan Negara (BTN) Yogyakarta Branch Office, it also looks at how motivation, workplace culture, and environment all affect worker performance. A quantitative descriptive approach was used, with a population comprising 50 employees from the BTN Yogyakarta Branch. The study employed a census sampling method, involving all 50 employees as respondents. Data sources included primary data gathered through direct questionnaires and secondary data from journals, books, theses, and online sources. The research utilized multiple linear regression analysis, along with tests for validity, reliability, classical assumptions, correlation coefficient (R), adjusted determination coefficient (R Square), and F and t tests. SPSS version 25 for Windows was applied to analyze the data. Through a significance value of 0.000 < 0.05, the F test findings showed that employee performance at the BTN Yogyakarta Branch is highly impacted by work motivation, work culture, and work environment, supporting the acceptance of H1. With significance values of 0.004, 0.003, and 0.004, respectively, the t test demonstrated that employee performance is highly impacted by work motivation, work culture, and work environment, supporting the acceptability of H4.